SISTEM PENGOLAHAN DATA UJIAN DI BIRO ADMINISTRASI AKADEMIK UNIVERSITAS SAHID SURAKARTA - Irma Dhamayanti; Dwi Retnoningsih; Sri Huning Anwariningsih (JURNAL GAUNG INFORMATIKA, 2016)
The Directorate of Academic University Sahid of Surakarta as academic data processing center has a very important role in supporting all the academic activities. During this time there were frequent difficulties for officials from the Directorate of Academic Sahid University of Surakarta in the service process especially if the test data to be processed is quite numerous and complex. This system is built using PHP and MySQL as the database This system is expected to be a facility that supports the service process Sahid exams at the University of Surakarta. Software development methods using waterfall method. The purpose of this final project is to produce a Service System Exam Sahid University of Surakarta. Thissystem contains data study program, the data curricula, the data lecturers, distribution data subjects, the student data, the data space, the data KRS, and data supervisor, the exam schedule, the test card, recaps invigilator, reports exam schedules and recap reports invigilator, Testing is done by using black box testing.